PENGARUH INTENSITAS ASET BIOLOGIS, KUALITAS AUDIT, DAN FIRM SIZE TERHADAP PENGUNGKAPAN ASET BIOLOGIS PADA SEKTOR AGRIKULTUR DI BURSA EFEK INDONESIA - Kusuma Indawati Halim (LPPM Universitas Bina Bangsa, 2022)
The financial statements reflect the company's position so that it can assist the user in analyzing the company's performance. Accounting policies related to biological assets should be presented so that users can understand transactions and performance of biological assets. This study aims to examine the effect of biological asset intensity, audit quality, and firm size on the disclosure of biological assets. This type of research is associative research. The population in this study were 24 companies in the agricultural sector on the Indonesia Stock Exchange from 2014 to 2018. The research sample was 14 companies determined by the purposive sampling method. The data analysis technique used multiple linear regression analysis. The test results show that the intensity of biological assets and firm size have a positive effect on the disclosure of biological assets, while audit quality has no effect on the disclosure of biological assets